The relevance of human rights council special sessions: the protection of the civilian population in current internal armed conflicts - Roque, Sónia (2019)
This article focuses on the analysis of the first decade (2006-2016) of the Human Rights Council (HRC) work. We analyze particularly the relevance of the HRC special sessions in what concerns to the protection of civilians in current non-international armed conflicts (NIAC). The HRC, that replaced the Commission on Human Rights, was established by the United Nations General Assembly (UNGA) Resolution 60/251 adopted on 15 March 2006. This institutional reshaping intended to transform the HRC into an action-oriented body, in an attempt to give a more effective and rapid response to global human rights (HR) protection challenges. Following the 2004 Report of the High-Level Panel on Threats, Challenges and Change, the United Nations General-Secretary Kofi Annan drew attention to the fact that a decisive moment for the United Nations (UN) had began. Kofi Annan highlighted in particular the need to fulfill the aspirations established in the United Nations Charter (UNC), and emphasized in general terms the challenges facing HR protection, particularizing the protection of the civilian population given the complexity of our days armed conflicts. Therefore the HRC appears in this line of institutional restructuring. The special sessions are one of the working methods of the HRC which allows the consideration of gross HR violations that need attention and require an urgent decision-making. The author argues that the analysis of these sessions is particularly relevant, because it allows us, on the one hand to examine which situations were analyzed, and on the other hand the different positions regarding this decision-making method that has not always proved consensual. I also argue that this decision-making procedure reflects some opportunities and faces challenges in trying to deal with the different perspectives of the actors within the HRC.